OUR PRACTICE OF FIXING A POSTERIOR CHAMBER IOL AFTER PHACOEMULSIFICATION OF THE CATARACT COMPLICATED BY DAMAGED LENS CAPSULE SUPPORT. CLINICAL CASES - A. A. Kozhukhov; D. O. Kapranov; M. V. Kazakova (Российский офтальмологический журнал, 2018)
Clinical cases of posterior chamber IOL fixation after phacoemulsification of cataract complicated by violated capsular support of the lens are described. The method developed by the authors, consists in locating the fixing unit in the corneal paracentesis and is shown to be effective and low traumatic. For citation: Kozhukhov A.A., Kapranov D.O., Kazakova M.V. Our practice of fixing a posterior chamber IOL after phacoemulsification of the cataract complicated by damaged lens capsule support. Clinical cases. Russian ophthalmological journal. 2018; 11 (2): 54-7. doi: 10.21516/2072-0076-2018-11-2-54-57 (In Russian).